ARCHITECTURE AND POSSIBILITIES OF ATTITUDE SYSTEM OF UNMANNED AND ULTRALIGHT AIR VEHICLES BASED ON SENSITIVE ELEMENTS OF NEW GENERATION - Y.A. BATISHCHEV; V.V. DUDNIK; A.S. GURINOV; A.S. KOPKIN (Вестник Донского государственного технического университета, 2018)
The architecture and building possibilities of attitude system of unmanned and ultralight air vehicles based on modern inertial sensors are considered. Executed development testing has corroborated possibility of using micromechanic sensors for the construction of an inexpensive inertial navigation system for unmanned and ultralight air vehicles.